Comparison of risk factors related to intraventricular hemorrhage between preterm infants born after normal and in vitro fertilization conceptions, a historical cohort study - Shariat, Mamak; Mohagheghi, Parisa; Khazaee, Sohrab; Nakhostin, Maryam; Farahani, Zahra; Khalesi, Nasrin (Iranian Journal of Child Neurology, 2019)
Objectives: Recent studies have shown an association between IVH and in-vitro fertilization (IVF) treatment. Objectives: The purpose of our study was to compare the level of significance of risk factors related IVH between preterm infants born after IVF and non-IVF conceptions. Material and Methods; a historical cohort study was done at 4 Iranian Hospitals in 2013-2014. Based on medical records 155 preterm newborns were divided into case (IVF) and control (normal conception) groups. Both groups' demographic data were extracted and recorded. The incidence of IVH and its' grades were compared between case and control groups. Significant related risk factors were also considered. Results: With regard to demographic characteristics, no differences were observed between 2 groups except for gestational age and mode of delivery (p<.05). The incidence of IVH especially grade II and III were significantly higher in the case group (P = 0.003). Results showed no correlations between GA, birth weight and number of gestations with the incidence of IVH in the case group (0.059, 0.85 and 0.49, respectively).On the other hand among GA, birth weight and number of gestations; multi gestations (p value=0.0001) was an effective risk factor for IVH occurrence in the controls. Conclusion; Results showed that the incidence of IVH in the IVF group was significantly higher than in the non-IVF group. IVF as an independent risk factor may cause high-grade IVH; however, in the controls, multi gestational pregnancy (p value=0.0001) was an effective risk factor for IVH occurrence.